2005
DOI: 10.1182/blood-2005-03-1197
|View full text |Cite
|
Sign up to set email alerts
|

Amnionless function is required for cubilin brush-border expression and intrinsic factor-cobalamin (vitamin B12) absorption in vivo

Abstract: IntroductionAdult-onset gastrointestinal malabsorption of the essential micronutrient, cobalamin (vitamin B 12 ), leads to potentially lethal manifestations as diverse as megaloblastic anemia and neutropenia, degeneration of spinal cord nerve tracts, and dementia. 1 In the very young, signs of cobalamin malabsorption may also include growth retardation or loss of developmental milestones or both. ImerslundGräsbeck syndrome (I-GS; also called megaloblastic anemia 1, OMIM no. 261100) is an autosomal recessive d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
119
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(123 citation statements)
references
References 41 publications
3
119
0
1
Order By: Relevance
“…This interdependency of cubilin and amnionless in cubilin brushborder expression has also been shown in a spontaneous Imerslund-Gräsbeck canine model with a mutated AMN homolog. 23 Our cases with a compound mutation in AMN and no mutation in CUBN provide the first evidence in humans that cubilin depends on AMN for its correct expression in the epithelium of the proximal tubule. An inverse situation was recently reported where the altered interdependency of both proteins was due to a CUBN mutation in exon 23 and no mutation in AMN.…”
Section: Resultsmentioning
confidence: 99%
“…This interdependency of cubilin and amnionless in cubilin brushborder expression has also been shown in a spontaneous Imerslund-Gräsbeck canine model with a mutated AMN homolog. 23 Our cases with a compound mutation in AMN and no mutation in CUBN provide the first evidence in humans that cubilin depends on AMN for its correct expression in the epithelium of the proximal tubule. An inverse situation was recently reported where the altered interdependency of both proteins was due to a CUBN mutation in exon 23 and no mutation in AMN.…”
Section: Resultsmentioning
confidence: 99%
“…This is a rare autosomal recessive disorder which, if left untreated, results in failure to thrive, megaloblastic anemia, proteinuria, and neurological damage 2. In dogs, primary cobalamin malabsorption, which is analogous to IGS in humans, has been reported in young Australian Shepherds,3 a Beagle,4 Border Collies,5, 6, 7 and Giant Schnauzers 8. The genetic defects in affected Border Collies and Beagles recently have been identified as 2 independent mutations in the CUBN gene 9, 10.…”
mentioning
confidence: 99%
“…As previously reported by Fordyce et al (2000), this patient was successfully treated by parenteral vitamin B12 administration every 2-4 weeks. Cobalamin malabsorption has also been described in giant Schnauzers (Fyfe et al, 1991), Border collies (Battersby et al, 2005), and Australian shepherd dogs (He et al, 2005). Investigations of affected Giant schnauzers and Australian shepherd dogs at the molecular level (Fyfe et al, 2004;He et al, 2005) have confirmed that this disease is a true homologue of congenital megaloblastic anaemia due to vitamin B12 deficiency because of a defect in the vitamin B12/intrinsic factor receptor (Imerslund-Gräsbeck syndrome) in humans.…”
Section: Diagnostic Proceduresmentioning
confidence: 64%
“…Cobalamin malabsorption has also been described in giant Schnauzers (Fyfe et al, 1991), Border collies (Battersby et al, 2005), and Australian shepherd dogs (He et al, 2005). Investigations of affected Giant schnauzers and Australian shepherd dogs at the molecular level (Fyfe et al, 2004;He et al, 2005) have confirmed that this disease is a true homologue of congenital megaloblastic anaemia due to vitamin B12 deficiency because of a defect in the vitamin B12/intrinsic factor receptor (Imerslund-Gräsbeck syndrome) in humans. This disease is caused by mutations in either the gene encoding cubilin (Aminoff et al, 1999) or amnionless (Tanner et al, 2003).…”
Section: Diagnostic Proceduresmentioning
confidence: 64%